The Effect of Science Technology Society (STS) Learning On Students’ Science Process Skills - Dewi, Ni Putu Laksmi Cintya; Atun, Sri (SCAD Independent, 2019)
This study aims to determine the effect of the application of Science Technology Society (STS) learning in high school students of class XI IPA. This research is a quasi-experimental research using posttest only design. The sample used is 64 students from Senior High School in Bantul district, Yogyakarta. Samples were obtained using purposive random sampling. Data were collected using posttest value to determine the effect of Science Technology Society (STS) learning and using Student Worksheet to know student ability. The data were analyzed by using ANOVA. The results showed that Science Technology Society (STS) study had significant effect, with a significance value 0,043 (p<0,05). Based on these studies, it can be concluded that the learning Science Technology Society (STS) influential in students’ science process skills.